2021
DOI: 10.1038/s41467-021-24418-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of the PZP domain of AF10 in acute leukemia driven by AF10 translocations

Abstract: Chromosomal translocations of the AF10 (or MLLT10) gene are frequently found in acute leukemias. Here, we show that the PZP domain of AF10 (AF10PZP), which is consistently impaired or deleted in leukemogenic AF10 translocations, plays a critical role in blocking malignant transformation. Incorporation of functional AF10PZP into the leukemogenic CALM-AF10 fusion prevents the transforming activity of the fusion in bone marrow-derived hematopoietic stem and progenitor cells in vitro and in vivo and abrogates CALM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…LAP was shown to mediate protein-protein interactions and homo-oligomerization of recombinant MLLT10 in vitro (40). Recently, disruption of LAP in MLLT10 fusion proteins was found to lead to malignant transformation (41). Towards its C-terminal end (amino acids 731-794 in NP_004632.1), the MLLT10 protein has a coiled-coil domain which contains a conserved octapeptide (EQLLERQW) motif separated by a short non-conserved sequence from a leucine zipper domain (42).…”
Section: Discussionmentioning
confidence: 99%
“…LAP was shown to mediate protein-protein interactions and homo-oligomerization of recombinant MLLT10 in vitro (40). Recently, disruption of LAP in MLLT10 fusion proteins was found to lead to malignant transformation (41). Towards its C-terminal end (amino acids 731-794 in NP_004632.1), the MLLT10 protein has a coiled-coil domain which contains a conserved octapeptide (EQLLERQW) motif separated by a short non-conserved sequence from a leucine zipper domain (42).…”
Section: Discussionmentioning
confidence: 99%
“…Two PHD fingers linked by a single zinc finger form an integrated module, the PZP domain (PHD-Zn-knuckle-PHD). Structural studies of PZPs from BRPF1, AF10, and PHF14 reveal a very similar saddle-like globular fold of this domain, which is stabilized by five zinc-binding clusters ( 49 , 50 , 51 , 52 , 53 ), and all PZPs have been shown to bind to unmodified histone H3 tail, but not identically. While the first PHD finger (PHD1) of PZP from BRPF1, AF10, and PHF14 interacts with the N-terminal region of H3 (residues A1-T6) in a manner similar to a typical PHD finger, PZPs of AF10 and PHF14 also recognize the middle region of histone H3 tail (residues L20-S28) ( Fig.…”
Section: Recognition Of H3(1–6) and H3(20–28) By Pzpmentioning
confidence: 98%
“…In-depth biochemical and in vivo analyses of PZPs underscore the significance of the interactions of this domain for proper functions of the PZP-containing proteins, including BRPF1/2/3, AF10/AF17, JADE1/2/3, and PHF14. AF10/A17 is a cofactor of the H3K79 methyltransferase DOT1L, and binding of AF10/AF17 PZP to H3 is required for H3K79 dimethylation and spreading of the H3K79me2 mark ( 49 , 52 ). It has been shown that PZP of AF10 engages the nucleosome through multivalent interactions with the entire H3 tail as well as DNA and that incorporation of functional PZP in leukemogenic CALM-AF10 fusions blocks the transforming activity in vitro and in vivo and abolishes CALM-AF10–driven leukemogenesis in vivo ( 52 ).…”
Section: Biological Importance Of the Pzp–h3 Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PHD1-zinc-knuckle-PHD2 (PZP) domain of AF10 is consistently interrupted in CALM-AF10 translocations. It has been recently identified that the disruption of the PZP domain of AF10 disrupts the normal localization of DOT1L across the genome, allowing DOT1L to be tethered to the HOXA locus by CALM-AF10 (28). CALM-AF10 leukemias typically show a poor response to therapy, have an increased propensity to relapse and have a worse overall prognosis.…”
Section: Calm-af10 Transformed Cells Exhibit Enhanced Cell Migrationmentioning
confidence: 99%